ANALYSIS OF THE IMPACT OF HIDROLOGICAL SPACE FUNCTION CHANGE ON WATER BALANCE CASE OF CEKUNGAN BANDUNG - Widiati (NIM : 25395012), Ati
Abstract : Rapid growth of development with finite of land availability have made many land convertion in Cekungan Bandung. It has to be researched in order to know how much it impact on water balance. Analysis of trend pattern and interaction between debit ((2), rain storm (P), run off coefficient (C), and land use have applied in this study. The method that use to described the trend pattern of lti P, and Cis correlation and liner regression. Map overlay (geologycal map, slope, rain storm, and land use map) is used to make new polygons that have a same character of watershed, in order to simplify in analysis of interaction between land use and water balance. The hydrologycal classification is based on the comparison between C value in natural condition and C value in actual condition. The result show that there are trend of decrease of daily minimum debit (with regresion coefficient -0.2709 and determination coefficient 0.8297 for IOs years), trend of increase of daily maximum debit (with regression coefficient 5.5138 and determination coefficient 0.9129 for IOs years), and rain storm is random. Land convertion have increase C value (from 0.4721 in 1986 to 0.4987 in 1992). The hydrological condition classification in case study show that 14.11% area with good category, 60.19% area with normal category, 23.63% area with start to critical, and 0.07% area with adequate criticaL